The impact of lean six sigma practices based on industrial revolution 4.0 towards balanced scorecard indicators in Malaysia manufacturing sector - Zamri, Shafeeka Fadlikh (2021)
Lean Six Sigma (LSS) presently was perceived as vital engines that drive performance excellence within manufacturing sector in the era of industrial revolution 4.0 (IR 4.0). Nonetheless, performance of Malaysia manufacturing sector was found to be descending particularly on its industrial production index (IPI), labour productivity and competitiveness ranking. Even though copious empirical studies were conducted on the success factor of LSS yet only few had anchored on the manufacturing sector especially in developing countries. Henceforward, the utmost purpose of this research was to propose a conceptual framework of LSS with the presence of tools and techniques (TATs) as mediator and IR 4.0 was tested as the moderator towards achieving first class performance by adapting Balanced Scorecard (BSC) indicators. Institutional, system and contingency theories were applied in this research. Five main hypotheses were proposed to develop conceptual framework based on structural equation modelling (SEM). Data were acquired from 205 manufacturing companies with 68.3% response rate. The structural model findings revealed that LSS had significant impact on BSC indicators with p-value<0.001. The indirect effect of TATs was found to be partially mediated on the relationship between LSS and BSC indicators with variance accounted for (VAF) value of 53.6%. Based on the moderating test, IR 4.0 was found to have insignificant results with p-value<0.05. Moreover, findings achieved in this research provided cognizance on how to intensify LSS through the integration of new body of knowledge such as TATs for better performance within Malaysian manufacturing sector. Ultimately, this research served the Malaysian manufacturing companies on a finer gists n improvising quality and overview regarding the implementation of LSS.